Metrics of sleep apnea severity: beyond the apnea-hypopnea index. Issue 7 (9th March 2021) - Malhotra, Atul; Ayappa, Indu; Ayas, Najib; Collop, Nancy; Kirsch, Douglas; Mcardle, Nigel; Mehra, Reena; Pack, Allan I; Punjabi, Naresh; White, David P; Gottlieb, Daniel J
Abstract: Obstructive sleep apnea (OSA) is thought to affect almost 1 billion people worldwide. OSA has well established cardiovascular and neurocognitive sequelae, although the optimal metric to assess its severity and/or potential response to therapy remains unclear. The apnea-hypopnea index (AHI) is well established; thus, we review its history and predictive value in various different clinical contexts. Although the AHI is often criticized for its limitations, it remains the best studied metric of OSA severity, albeit imperfect. We further review the potential value of alternative metrics including hypoxic burden, arousal intensity, odds ratio product, and cardiopulmonary coupling. We conclude with possible future directions to capture clinically meaningful OSA endophenotypes including the use of genetics, blood biomarkers, machine/deep learning and wearable technologies. Further research in OSA should be directed towards providing diagnostic and prognostic information to make the OSA diagnosis more accessible and to improving prognostic information regarding OSA consequences, in order to guide patient care and to help in the design of future clinical trials.